Potrzeby informacyjne samorządu terytorialnego - wyzwanie dla statystyki publicznej - Obrębalski, Marek (Information needs of local self-government as a challenge for public statistics, 2006)
Research on statistical information needs across local self-government should fulfil at least a few basic tasks, these including: creation of possibly optimum thematic range of statistical information, with regard to the demand reported; consideration of the level and range of differentiation of demand, as represented by various circles of national, regional, and local level; response to the needs of economic and social systems created by the mechanisms of market economy. The analysis of demand range shows that some suggestions are of clearly marketing nature. However, some suggestions perceived by local self-government make a range of challenge for public statistics. It also indicates the growing importance of statistical information in taking short- and long-term decisions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1142, s. 144-153